Free Triiodothyronine Connected With Metabolic Changes in Patients With Coronary Artery Disease by Interacting With Other Functional Indicators - Tian, Xiao-xue; Zheng, Shu-fen; Liu, Ju-e; Wu, Yuan-yuan; Lin, Lu; Chen, Hong-mei; Li, Li-wen; Qin, Min; Wang, Zi-xian; Zhu, Qian; Lai, Wei-hua; Zhong, Shilong (Frontiers in Molecular Biosciences, 2021)
This study aims to evaluate the association between free triiodothyronine (FT3) and outcomes of coronary artery disease (CAD) patients, as well as to assess the predictive power of FT3 and related functional markers from the perspective of potential mechanism. A total of 5104 CAD patients with an average follow-up of three years were enrolled into our study. Multivariate Cox regression was used to evaluate the associations between FT3, FT4 (free thyroxin), FT3/FT4 and death, MACE. We developed and validated an age, biomarker, and clinical history (ABC) model based on FT3 indicators to predict the prognosis of patients with CAD. Multivariable Cox proportional hazards model found that FT3 and FT3/FT4 were independent predictors of mortality (Adjusted HR = 0.624, 95% CI = 0.486–0.801; adjusted HR = 0.011, 95% CI = 0.002–0.07, respectively). We also found that emerging markers pre-brain natriuretic peptide, fibrinogen, and albumin levels are significantly associated with low FT3 (P <0.001). The new risk death score based on biomarkers can well predict the outcomes of CAD patients (C index of 0.764, 95% CI = 0.731–0.797). Overall, our findings suggest that low level of FT3 and FT3/FT4 are independent predictors of death and MACE risk in CAD patients. Besides, prognostic model based on FT3 and other provides a useful tool for the death risk stratification of CAD patients.